A geração de energia fotovoltaica na estância Guatambu em Dom Pedrito - RS: uma análise pela ótica das eco-inovações - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Considering the growing importance and contemporaneity of the discussions on ecoinnovations, as well as the relevance of a possible reduction of production costs for an industrial company, the main objective of this paper is to analyze, from the point of view of eco- innovations, the process of installing a system of electricity generation through photovoltaic panels at Estância Guatambu, a winery located in the city of Dom Pedrito - RS. A "case study" type of research was carried out, using a qualitative and quantitative approach. Data collection included a semi-structured interview, bibliographical and documentary research and visits to the winery, where the determinants that led to the adoption of this power generation system were observed. Initially, it was described how the process of decision and installation of the system was given, along with a brief history of the firm. Next, an economic and financial feasibility analysis of the investment was carried out, based on official company documents, which showed the feasibility of the investment and the return on capital invested in 10 years. Finally, based on the specific characteristics of the eco-innovations, which are exposed in the theoretical framework of this research, an evaluation was made on the Estância Guatambu case, justifying its characterization as an eco-innovation based on their determinants. In addition to this classification, a synthesis of the economic, social and environmental results that this innovation has produced up to the present moment was also elaborated, such as considerable market gains and the reduction of the emission of polluting gases.
Keywords: Eco-inovações; Viabilidade Econômica; Sustentabilidade; Eco-innovations; Viability Economic; Sustainability; CNPQ::CIENCIAS SOCIAIS APLICADAS